Histopathological characterization of abdominal aortic aneurysms from patients with multiple aneurysms compared to patients with a single abdominal aortic aneurysm - Körfer, Daniel; Erhart, Philipp; Dihlmann, Susanne; Hakimi, Maani; Böckler, Dittmar; Peters, Andreas (Biomedicines, 2023)
The aim of this study was to investigate histopathological differences in abdominal aortic aneurysms (AAAs) between patients with multiple and single arterial aneurysms, as we suspect that there are different underlying mechanisms in aneurysm formation. Analysis was based on a previous retrospective study on patients with multiple arterial aneurysms (mult-AA; defined as at least four, n = 143) and a single AAA (sing-AAA, n = 972) who were admitted to our hospital for treatment between 2006 and 2016. Available paraffin-embedded AAA wall specimens were derived from the Vascular Biomaterial Bank Heidelberg (mult-AA, n = 12 vs. sing-AAA, n = 19). Sections were analyzed regarding structural damage of the fibrous connective tissue and inflammatory cell infiltration. Alterations to the collagen and elastin constitution were assessed by Masson-Goldner trichrome and Elastica van Gieson staining. Inflammatory cell infiltration, response and transformation were assessed by CD45 and IL-1β immunohistochemistry and von Kossa staining. The extent of aneurysmal wall alterations was assessed by semiquantitative gradings and was compared between the groups using Fisher’s exact test. IL-1β was significantly more present in the tunica media in mult-AA compared to sing-AAA (p = 0.022). The increased expression of IL-1β in mult-AA compared to sing-AAA indicates inflammatory processes play a role in aneurysm formation in patients with multiple arterial aneurysms.
Gesehen am 18.08.2023